Chronic spontaneous non-aneurysmal aortic rupture treated with endovascular surgery - Bruno Jeronimo Ponte; Viviane Galli Dib; Andressa Cristina Sposato Louzada; Júlia Freire Castanheiras de Paiva Ferreira; Lucas Lembrança Pinheiro; Cynthia de Almeida Mendes; Nelson Wolosker (Einstein (São Paulo))
ABSTRACT Spontaneous non-aneurysmal aortic rupture is rare and is usually attributed to penetrating aortic ulcers, infections, tumor infiltrations, or inflammatory and collagen diseases. Chronic rupture is infrequent but extremely rare in non-aneurysmal aortas, which makes diagnosis difficult because the absence of an aneurysm can mislead the physician to rule out rupture. Here, we describe the case of an 85-year-old male, who was undergoing oncological investigation for weight loss, inappetence, and back pain. Computed tomography and magnetic resonance imaging performed 3 months before admission showed a contained pseudoaneurysm of the infrarenal aorta associated with significant aortoiliac calcification and images suggestive of peritoneal implants. The patient was referred to our oncological center and underwent abdominal computed tomography for oncological investigation and staging. The patient was urgently admitted to the intensive care unit after a critical finding of contained rupture of the infrarenal aorta during the scan. Endovascular repair was indicated, and the patient was successfully treated with implantation of an Endurant IIs 25 × 25 × 70 mm endoprosthesis. No procedural complications were observed. Postoperative course was uneventful, and the patient was discharged on the fifth postoperative day. Control computed tomography performed 1 and 6 months after surgery showed no leaks. This case emphasizes the importance of communication between the radiologists and attending physicians. As the rupture was punctual and well defined in the computed tomography and angiography images, endovascular repair with an aortic cuff was safely performed, and the procedure time was reduced.